2019
DOI: 10.1002/jnm.2616
|View full text |Cite
|
Sign up to set email alerts
|

An approach for determining thermal resistance model parameters of SiGe HBT

Abstract: This paper presents an improved method for determining the thermal resistance and junction temperature for silicon germanium heterojunction bipolar transistors. This method is a full analytical procedure without any iteration based on a set of accurate expressions. The thermal resistance is tested against iterative and analytic methods reported before. Good agreement is obtained between simulated and measured results for three SiGe devices with different emitter geometries.KEYWORDS analytic method, back end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Equivalent models are usually used to simulate the physical device work process when analyzing a device like HBT [ 3‐5 ] . The equivalent circuit model is a shortcut for people to understand the characteristics of devices and computing ports [ 6 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Equivalent models are usually used to simulate the physical device work process when analyzing a device like HBT [ 3‐5 ] . The equivalent circuit model is a shortcut for people to understand the characteristics of devices and computing ports [ 6 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al presented a review on the compact modeling of InP HBTs for THz integrated circuits. Useful improvements made for HBTs are reported on the analysis of intrinsic base resistances by Chen et al, on large‐signal models by Hu et al, on the determination of cutoff and maximum oscillation frequencies by Zhang and Gao, and on the thermal resistance calculation by Wang et al Due to a high breakthrough voltage and saturation velocity, GaN HEMTs is very promising for millimeter‐wave solid‐state power amplifiers. Chen et al reported an improved quasi‐physics zone division large‐signal model to account for electro‐thermal effects, which is valid for the ambient temperature range of 245 to 390 K. Physical parameters' effects, reliable parameter extraction, and dynamic thermal impedance extraction for the equivalent circuit models of GaN HEMTs are discussed by Mi et al, Chen et al, and Wang et al, respectively.…”
mentioning
confidence: 99%